1963
DOI: 10.3181/00379727-113-28370
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Resistance to Tumor Cells after Stress, Followed by Increased Resistance.

Abstract: DECREASED RESISTANCE TO TUMOR CELLS 377have been obtained with mitochondria from liver.As proposed in the drawing of Fig. 3, an increased rate of influx of labeled anions with acidification, or of cations with alkalinization, might be anticipated on the basis of change in permeability due to change in surface charge. Alteration in permeability would affect bidirectional flux and would serve to explain the changes with potassium, at least in the range between pH 7.2 and 8.5. On the other hand, if a net increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1965
1965
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Lymphoid cells obtained from rats subjected to bums or surgical injury are unable to manifest graft-vs.-host reactions in recipient rats differing at a minor histocompatibility locus (22). The incidence of tumor take (23,24) and spontaneous metastases (25) is increased when tumorinjected animals are subjected to surgical operations. The number of T lymphocytes is significantly decreased after burns as measured by rosette formation with sheep erythrocytes (26).…”
Section: Resultsmentioning
confidence: 99%
“…Lymphoid cells obtained from rats subjected to bums or surgical injury are unable to manifest graft-vs.-host reactions in recipient rats differing at a minor histocompatibility locus (22). The incidence of tumor take (23,24) and spontaneous metastases (25) is increased when tumorinjected animals are subjected to surgical operations. The number of T lymphocytes is significantly decreased after burns as measured by rosette formation with sheep erythrocytes (26).…”
Section: Resultsmentioning
confidence: 99%
“…Minster (28) found that the take of cancer cells injected subcutaneously in rats was greatly increased at the time of stress (celiotomy and nembutal anesthesia), gradually decreased to control value of non-operated rats about the 8th day, and reached a maximal resistance at about 18th day. Then the resistance to take gradually returned to control level within the next 10 days.…”
Section: Studies Of Surgical Stress In Experimental Animalsmentioning
confidence: 99%